The Construct of Health Communication Effectiveness and Its Dimensions: A Confirmatory Factor Analysis within Hospital Settings in Middle Eastern Conflict Zones - Suranta Bill Fatric Ginting; Eldha Novarina Tarigan; Joyce Yulianti Silalahi; Luthfiah Mawar; M. Agung Rahmadi; Helsa Nasution (PT Inovasi Pratama Internasional, 2026)
This study aims to empirically substantiate the dimensional structure of health communication effectiveness in hospitals operating within conflict zones in the Middle East through a Confirmatory Factor Analysis (CFA) approach. Secondary data were compiled from 847 medical records and patient surveys drawn from twelve hospitals in Syria, Iraq, and Yemen between 2019 and 2023. The six-dimension CFA model demonstrated exceptionally robust statistical adequacy, indicated by χ²/df = 2.134, CFI = 0.954, TLI = 0.947, RMSEA = 0.042 (90% confidence interval: 0.038-0.046), and SRMR = 0.039. Information clarity emerged as the strongest dimension with a factor loading of λ = 0.891, followed by provider empathy, responsiveness, communication competence, accessibility, and cultural sensitivity, all of which were significant at p < 0.001. Construct reliability was high, with CR = 0.943 and AVE = 0.735. These findings reinforce the work of Epstein et al. (2010) and Street et al. (2009) on the critical importance of patient-centered communication, while extending the current discourse by integrating cultural sensitivity and trauma-informed communication principles that have not yet been examined in conflict settings. This study offers a novel contribution by comprehensively validating the health communication construct in the context of extreme armed conflict